Synthesis and Computational Study of Some New 1-(1H-indol-1- yl)ethanone Derivatives on COX-2 Enzyme and Evaluation of In-Vivo Analgesic and Anti-inflammatory Activity - Kumar, Arvind; Kumar, Deepika; Porwal, Mayur; Mishra, Arun K. (Letters in Drug Design & Discovery, 2023)
Background: Indole and its derivatives play an important role in the synthesis of commercially relevant intermediate molecules required for the synthesis of a wide range of bioactive molecules. Aim: Exploration of the synthesis of novel nonsteroidal anti-inflammatory drugs, as well as their computational studies and pharmacological effects, was aimed as an important component of the present research. Objective: The objective of the present work was to synthesize some novel 1-(1H-indol-1-yl)ethanone compounds, analyze their computational effects on the COX-2 enzyme and test their in vivo analgesic and anti-inflammatory activity. Methods: The condensation of 4-(2-(1H-indol-1-yl)-2-oxoethoxy) benzaldehyde with substituted aniline in ethanol in the presence of a catalytic quantity of glacial acetic acid was performed, which yielded the new Indole derivatives. IR, NMR, mass spectroscopy and elemental analysis techniques were used to characterize the structures of new indole derivatives. To estimate the drug-like candidate’s nature, a number of molecular attributes of these derivatives were computed. The synthesized derivatives were docked with a specific reference cyclooxygenase-2 (COX-2) enzyme. The physical similarity of the newly synthesized derivatives (D1-D8) and indomethacin (the reference drug) was determined by evaluating seven physicochemical features by a software. Results: Although the bioavailability/drug likeness was found to be in the standard range, the synthesized compounds exhibited close similarity with those of the reference drug, and subsequent optimization was necessary. Conclusion: The newly synthesized indole derivatives as COX-2 inhibitors were evaluated for their biological properties, which included anti-inflammatory and analgesic efficacy. Other: D-7 (1-(1H-indol-1-yl)-2-(4-((4-nitrophenyl)imino)methyl)phenoxy)ethanone) was found to have the strongest anti-inflammatory and analgesic activity amongst the eight target compounds.
Keywords: COX-2 inhibitors